The Effectiveness of a Group Behavioral Psychotherapy Program in Reducing the Level of Psychological Loneliness among a Sample of Special Education Female Students - Al-Mazouq, Hannan Belied; Ben Khair, Fathia (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The study aimed to develop a behavioral therapeutic program and determine its effectiveness in reducing the feeling of psychological loneliness among female students of Special Education at the Faculty of Human Science for Girls, Alasmarya Islamic University, in the city of Zliten, during the period from November 17, 2022, to January 19, 2023. It also sought to identify the differences between the experimental and control groups in psychological loneliness. The main sample consisted of 16 female students from the Department of Special Education, equally divided between the experimental and control groups. The researchers adopted the experimental method and employed the Psychological Loneliness Scale and the Behavioral Counseling Program. The study concluded that there were no statistically significant differences between the two groups. Accordingly, no differences appeared between the pre- and post-test results of the two groups. The lack of effectiveness of the program may be attributed to the deletion of several items from the scale—based on the decision of the supervisor and the evaluators—or to the lack of validity in the participants’ responses.
Keywords: Behavioral Therapy Program; Special Education; Psychological Loneliness